White light-driven photo response of TiO2 thin films: Influence of substrate texturing. (1st November 2018) - Singh, Ranveer; Kumar, Mohit; Saini, Mahesh; Satpati, Biswarup; Som, Tapobrata
Graphical abstract: Highlights: TiO2 films (having thicknesses of 5 and 20 nm) are grown on pristine - and chemically etched pyramidally- textured Si substrates for photo detector fabrication. Photo detector based on 20 nm-thick TiO2 / txt -Si heterojunction shows a remarkable enhancement in the photocurrent (76.68 µA). Photo response properties of TiO2 -coated txt -Si substrates are studied for their potential use in photodetector and a fast rise (0.32 s) and fall time (0.18 s) is observed. The present experimental results on conformally grown TiO2 film on textured -Si substrates will be extremely useful for photodetectors. Abstract: In this work, the role of film thickness on white light-driven photo response and electrical properties of TiO2 /Si heterojunctions is investigated. Two types of substrates, viz. pristine- and chemically prepared pyramidally textured-Si are used for simultaneous growth of TiO2 films using radio frequency (RF) magnetron sputtering technique. X-ray diffraction study reveals the amorphous nature of as-grown TiO2 thin films. In addition, it is observed that the surface reflectance of conformally grown TiO2 overlayers on textured-Si substrates can be brought down to 0.73% for 5 nm and 0.77% for 20 nm, whereas in case of p ris-Si substrates it is 40% for 5 nm and 30% for 20 nm-thick films (in the wavelength range of 400–800 nm). Further, TiO2 /Si heterostructures exhibit diode-like rectifying behavior under both dark and white light illumination. The 5 nm-thick films exhibit very low photoactivity in terms of photocurrent, whereas 20 nm-thick films show a remarkable enhancement in the photocurrent up to 10.25 and 78.68 μA (under reverse bias) when grown on pris -Si and txt -Si substrate, respectively. In addition to the transient photocurrent, the responsivity and sensitivity are also higher for 20 nm-thick films. These results are explained in terms of change in their optical and electrical properties. The present finding will be certainly important for fabricating high speed optoelectronic devices based on reverse biased TiO2 /Si heterojunctions.